The Role of Return on Assets on Sustainability Disclosure to Value of the Firm - Purwanti, Ari (Universitas Pendidikan Indonesia, 2018)
AbstractIn previous studies, it was proved that the disclosure of sustainability affected the value of the firm insignificantly. Therefore, this study aims to investigate whether Return on Assets can mediate the effect of sustainability disclosure on firm value. The sample of this study is companies that consistently presents Sustainability Reports from 2013 to 2015. The research hypothesis is tested using panel data regression. The results prove that the future Return on Assets can mediate the effect of sustainability disclosure on the future value of the firm.